What is Contemporary Art ? - Cameron, Dan (Malmö : Rooseum - Center for Contemporary Art, 1989)
Fischli & Weiss ; Fritsch, Katharina ; Gascoigne, Rosalie ; Guzman, Federico ; Herold, Georg ; Horn, Rebecca ; Kawara, On ; Kelley, Mike ; Klein, Astrid ; Koons, Jeff ; Kopystiansky, Igor ; Levine, Sherrie ; Miyajima, Tatsuo ; Obholzer, Walter ; Oppenheim, Meret ; Perejaume ; Steinbach, Haim ; Traylor, Bill ; Wall, Jeff
biog., tent. p. 195-206
Engels & Zweeds
What is Contemporary Art ?, Rooseum - Center for Contemporary Art, Malmö, 3/6 - 30/7/1989
boek